Pengaruh Pelayanan Unit Costumer Service dan Informasi terhadap Kepuasan Pelanggan PT Angkasa Pura Indonesia di Bandar Udara Adi Soemarmo Boyolali - Rohmadhani, Affit Aulia; Fakhrudin, Arif (Jurnal Manajemen Dirgantara, 2025)
This study aims to analyze the influence of Customer Service and Information unit services on customer satisfaction at PT Angkasa Pura Indonesia at Adi Soemarmo Airport, Boyolali. The method used is quantitative through a survey of 100 respondents who have used the service. Data analysis was carried out by testing validity, reliability, normality, linearity, simple linear regression, t-test, and coefficient of determination (R²) using SPSS. The results of the validity test indicate that all questionnaire items are valid, and the reliability test shows reliability. The data is stated to be normally distributed. The results of the regression test indicate that Customer Service and Information unit services have a significant effect on customer satisfaction, with a significance value of <0.05 and a coefficient of determination of 0.455. This means that 45.5% of customer satisfaction is explained by service variables, while the rest is influenced by other factors. The conclusion of this study is that improving the quality of Customer Service and Information services has an important role in increasing customer satisfaction in the airport environment.